2015
DOI: 10.1209/0295-5075/110/13001
|View full text |Cite
|
Sign up to set email alerts
|

Internuclear interaction on fully differential cross-sections for single ionization of helium by proton impact

Abstract: The modified Coulomb-Born approximation including the proton impact internuclear interaction (MCB-PI) is applied to study single ionization of helium by 75 keV proton impact. Fully differential cross-sections (FDCS) are calculated both in the scattering and perpendicular planes. The results are compared with experimental data and theoretical predictions from the three-body distorted wave (3DW) and the continuum distorted wave-eikonal initial state (CDW-EIS). It is shown that the features of the FDCS are better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…Similar conclusions were obtained in Ref. [15] in the modified Coulomb-Born approximation, where NN was also included (MCB-PI). Recently, within the framework of a Born-like approximation a continuum correlated wave (CCW) function has been applied for the final sate [16].…”
Section: Comparison To and Discussion Of Other Studiessupporting
confidence: 89%
See 3 more Smart Citations
“…Similar conclusions were obtained in Ref. [15] in the modified Coulomb-Born approximation, where NN was also included (MCB-PI). Recently, within the framework of a Born-like approximation a continuum correlated wave (CCW) function has been applied for the final sate [16].…”
Section: Comparison To and Discussion Of Other Studiessupporting
confidence: 89%
“…Dot dashed lines: 3C calculations [14]. Dot dot dashed lines: MCB-PI calculations [15]. Experiment: • from Ref.…”
Section: Comparison To and Discussion Of Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the PT interaction in the final state was not considered in the above mentioned calculations. In fact, it has been shown that the interaction between the projectile and the target ion, at intermediate impact energies, [8][9][10]20,21] has a large influence depending on the ejected electron energies and momentum transfer values. It is necessary to include the PT interaction at the level of multiple differential cross sections.…”
Section: Introductionmentioning
confidence: 99%